Associations between household educational attainment and adolescent positive mental health in Canada - Thomson, Kimberly C. (SSM Popul Health, 2017)
Investigating the determinants of positive mental health, as opposed to focusing on mental illness, is a new research direction with important implications for population health promotion. Past research suggests that mental health develops in early childhood and that social factors including highest household educational attainment may play an important role. The current study examined the association between household educational attainment and adolescent self-reported positive mental health in a nationally representative Canadian sample using data from the 2011-12 Canadian Community Health Survey. The sample included 10,091 adolescents aged 12 to19 living at home with at least one parent. Household educational attainment was obtained from a Statistics Canada derived variable documenting the highest level of education in the household. Adolescent positive mental health was assessed using the Mental Health Continuum scale. Multivariable logistic regression analyses showed that after adjusting for household income, single parent status, and household size, adolescents had lower odds of experiencing positive mental health in households in which attempted but not completed post-secondary was the highest education level compared to completed post-secondary education (OR = 0.64, 95% CI = 0.44, 0.95). This association was strongest in adolescents aged 12 to14 (OR = 0.43, 95% CI = 0.21, 0.84) and females (OR = 0.50, 95% CI = 0.29, 0.88). Contrary to expectations, we did not find an incremental increasing association between adolescent positive mental health and household educational attainment. Instead, results suggested that common underlying factors may have contributed both to uncompleted post-secondary education in the household and adolescents’ diminished positive mental health.